Pendidikan Kesehatan Cara Pencegahan Dan Penularan Penyakit Tb Dalam Upaya Peningkatan Unsur Diperlukan Tubuh (Mikroelemen) - Rahagia, Rasi; Kurniati, Eni; Hanif, Muhammad; Fatany, Alief Ihram; Indra, Indra; Anurogo, Dito (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Tuberculosis is an infectious disease caused by Mycobacterium Tuberculosis, which is a disease of the lower respiratory tract in which most tuberculosis bacilli enter the lung tissue through air bone infection and then undergo a process known as primary focus of ghon. The aim of PkM is to increase knowledge about pulmonary TB and also to prevent death, recurrence, resistance to OAT, and break the chain of transmission. Health education methods for preventing and transmitting TB disease in an effort to increase the elements needed by the body (microelements). The result of PkM is an increase in respondents' knowledge and behavior regarding pulmonary TB disease, both regarding the causes of pulmonary TB disease, symptoms, methods of transmission, prevention and ways to improve or improve the nutritional status of TB sufferers. Conclusion The community service team (PkM) really hopes that this activity can attract the attention of the local government and also the work area of ​​the community health center as a work program as a form of community service activity which aims to provide a solution to the TB disease problem.